Scheduling Program Analysis of Pressure Relief Device (PRD) According to RBI API 581 on Production Gas Separator System - Dwi Priyanta; Nurhadi Siswantoro; Muhammad Saifulloh (International Journal of Marine Engineering Innovation and Research, 2018)
Pressure relief device serves to control and limit the pressure by directing the flow into an additional path. In the process of purification of oil and gas, application of PRD are found in production gas separator system. However, based on API 581, the PRD also has a risk of failure that every oil and gas company needs to conduct regular inspections to ensure the reliability of PRD. One approach to evaluating critically the PRDs for arranging and scheduling programs is to use the risk-based inspection (RBI) method. The RBI is a systematic approach to the method of inspection management of equipment or works unit based on the level of risk that the equipment or work units. Risk assessment for production gas separator system’s PRD has based on API RP 581 third edition. After knowing the level of risk for PRD, the risk needs to be evaluated. For acceptable risk, it can be used as a reference to determine the next inspection until risk target. Meanwhile, unacceptable risk should be inspected immediately after RBI analysis.